Metaphorical Expression used in Poetry in book "The Everyday Poet" by Deborah Alma - Sinaga, Ayu Gres Oktavia; Marpaung, Marlin Steffi (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
Poetry is characterized as a kind of literature or creative writing that uses a variety of poetic approaches to stimulate the reader's emotions and imagination. This study focuses on the metaphorical expression used in poetry in the book "The Everyday Poet" by Deborah Alma. The objectives of this study are to determine the types of metaphors reflected in Deborah Alma’s poetry book "The Everyday Poet," to find out the most common types of metaphors used, and to explain the meaning of the metaphors contained in the poems. The methodology used in this study is descriptive qualitative research. The data were obtained through library research and a variety of literature to present a descriptive issue. The result of this study showed that there are twelve metaphors in the book "The Everyday Poet." There are six anthropomorphic metaphors, one animal metaphor, two abstract to concrete metaphors, and three synesthetic metaphors, and based on the data, the most commonly used metaphor is anthropomorphic metaphor, which has six lines in the book "The Everyday Poet" by Debora Alma.